An integrative approach to study on consumer behavior towards plug-in hybrid electric vehicles revolution: Consumer behavior towards plug-in hybrid electric vehicles - Adnan, N. (IGI Global, 2016)
Transport electrification has experienced major deviations for the last few decades. Current investigationtowards the implication of green technologies to decrease pollution and increase diffusion ofrenewable energy in the transportation sector are achieving more attention. The significance of plug-inhybrid electric vehicles (PHEVs) play a key role towards the policy option to reduce the environmentalconcern. There are major uncertainties in the diffusion of PHEVs timing of market distribution amongconsumers. However, there has been a considerable effort made towards the benefit of PHEVs demand.Yet, the debates on consumer behavioral economics towards the adoption of electric vehicles are lessrecognized. Researchers highlight the significance of PHEVs from a combined perspective consideringPHEVs which allows bi-directional flow of electricity. However, it mainly focuses on interface amongtechnology adoption and consumer behavior includes many other aspects such as individual adoptionbehavior, vehicles performance, environmental concern and power system demand. Â© 2017, IGI Global.